On the Multispecies Delayed Gurtin-MacCamy Model - Anna Poskrobko; Antoni Leon Dawidowicz (Abstract and Applied Analysis, 2013)
The paper deals with the description of multispecies model with delayed dependence on the size of population. It is based on the Gurtin and MacCamy model. The existence and uniqueness of the solution for the new problem of n populations dynamics are proved, as well as the asymptotical stability of the equilibrium age distribution.